Diffuse Cerebral Vasospasm After Aneurysmal Subarachnoid Hemorrhage in a 15-Year-Old Girl: A Case Report - Lee, Dajeong; Lee, Jeehun; Kim, Keon Ha; Kim, Ji Hye; Lee, Jiwon (Frontiers in Radiology, 2022)
Diffuse cerebral vasospasm after subarachnoid hemorrhage (SAH) is a complication resulting in an ischemic condition presenting with altered mentality and followed by motor or speech impairment. It is uncommon in pediatric population and requires differential diagnosis from Moyamoya disease, which is relatively common in Korea. We report a case of a 15-year-old girl who was presented with a seizure and subsequent headache, poor oral intake, and altered mentality, who was finally diagnosed with sporadic vasospasm followed by multiple aneurysm ruptures. The patient had recurrent seizures and persistent headache at the time of transfer. On the second day after transfer, she showed focal motor weakness and dysarthria, and her symptoms gradually progressed, showing paraplegia and aphasia on the third hospitalization day. Brain magnetic resonance imaging and magnetic resonance angiography demonstrated diffuse narrowing cerebral vasospasm of bilateral middle cerebral arteries, anterior cerebral arteries, and distal internal carotid arteries and three unruptured aneurysms. The patient was treated with intravenous hydration and nimodipine to expand the narrowed vessels. After confirming that the vessels were enlarged, we successfully executed the endovascular coil embolization. Her neurological deficits were improved through medical, interventional, and rehabilitation treatments and fully restored 11 months after discharge.